Investigation of biochemical and physiological parameters of the newborn Saiga antelope (Saiga tatarica) in Gansu Province, China - Liu, Xia (PLoS One, 2019)
BACKGROUND: The Saiga antelope (Saiga tatarica) is a critically endangered species, and there has been limited success in restoring the population by captive breeding. This study assessed the biochemical and physiological parameters of newborn Saiga antelope to provide reference information that can be used to evaluate their health. Comparisons have been made with parameters for horses and closely related members of the Bovidae family but there are no reference values for the newborn Saiga antelope. METHODS: Biochemical and physiological parameters were measured in 61 animals. An automatic analyzer (Hitachi Ltd. 7180 Serial, Tokyo, Japan) was used to analyze the biochemical parameters, while the Coulter counter (Model ZK) was used to analyze the physiological parameters. RESULTS: The results showed that the biochemical and physiological parameters differ considerably in range. The evaluation of parameters stratified by sex showed differences. Triglyceride and LDL cholesterol concentrations among male animals were significantly higher than those in female animals, while the creatine kinase concentrations were significantly higher in females than in males. Comparing this study’s results with published data for horses showed many similarities and some differences. Cholesterol, magnesium and glucose levels were similar between Saiga antelope and horses, while albumin and hematocrit levels in Saiga antelope differed from the reference values in horses. CONCLUSION: The study has shown that horses and even closely related members of the Bovidae family are not suitable references when evaluating the biochemical and physiological properties of newborn Saiga antelope. These animals have unique stressors and warrant further study to inform efforts pertaining to their care and the future sustainability of the species.